Prion An Overview - Tutar, Yusuf (IntechOpen, 2017)
Protein aggregation causes malfunction in several biochemical processes. Genetic and spontaneous formations of these transmissible spongiform encephalopathies are fatal to humans and animals. Conformational change of normal form of the protein to misfolded form causes its accumulation. The misfolded infectious protein agent forms the pathogenesis of the disease. This book presents pathology of the disease along with current knowledge of the structure-activity mechanism in the first two sections. Dyshomeostasis of metals is implicated in the pathogenesis of prions, and this influence is discussed further to understand the prion mechanism. Genetic resistance and immunobiology of the disease are elaborated in the following section. Finally, a computational study on the dynamics of the prion propagation provides a structural basis of the mechanism.